The Eight Mile Brook Plutonic Suite, Cobequid Highlands, Nova Scotia, Canada: Ordovician alkalic magmatism in Avalonia - White, Chris E.; Barr, Sandra M.; Archibald, Donnelly B. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The Eight Mile Brook Plutonic Suite (EMBPS) consists of co-mingled gabbroic, syenitic, and granitic rocks that intruded Tonian rocks of the Mount Thom Formation and Mount Ephraim Plutonic Suite at the southeastern edge of the Mount Ephraim block in the Cobequid Highlands. It is unconformably overlain by or in faulted contact with Carboniferous sedimentary rocks. In situ dating of zircon in three samples by laser ablation – inductively coupled plasma – mass spectrometry (LA-ICP-MS) yielded Early Ordovician concordia and weighted mean 207Pb/238U ages of about 480 Ma. Age and chemical similarities among the EMBPS, West Barneys River Plutonic Suite in the Antigonish Highlands, and the Cape Porcupine Complex suggest that all are closely related and formed by magma fractionation processes during an event that occurred between ca. 481 and 466 Ma based on previously published U–Pb zircon ages from thermal ionization mass spectrometry. The magmatism may be a far-field effect of subduction, a localized area of extension or a hot spot. Chemical and age differences between these plutonic suites and the bimodal volcanic Dunn Point and McGillivray Brook formations in the northwestern Antigonish Highlands suggest that the magmatism in these units may not be directly related. Minor gabbroic and syenitic intrusions in the northern Antigonish Highlands are undated but show chemical differences from the dated magmatic rocks and hence may not be related.